Extent of Participation of Respondents in Production and Broadcasting Programme of Community Radio - Krishna D.K., N.V. Kumbhare, R.N. Padaria, Premlata Singh and Arpan Bhowmik, (Indian Journal of Extension Education, 2018)
The community radio has made an impression in all grounds of rural society in which there was a need toassess socio-technological empowerment of rural households. The study was taken up to compare the statusof community members’ participation in community radios, operational under three different hosting agenciesi.e. State Agricultural University (SAU), Krishi Vigyan Kendra (KVK) and Non-Government Organization(NGO). The community radio stations namely Pantnagar Janvani (G.B. Pant University of Agriculture andTechnology), Pravara (KVK, Ahmednagar) and Yeralavani (Yerala Projects Society, Sangli) were selectedpurposively. Four villages have been selected randomly from one purposively selected block. Forty (40)respondents from four randomly selected villages from each CRS coverage area/ broadcast range along with10 staff members of each CRS were selected for the study. Thus, a total of 150 respondents constituted thesample for the study. About 43 per cent of respondents had low level of participation in programme productionand broadcasting followed by moderate level (40 %) and high level (17.50 %). Education and perceptionabout CRS programmes were significantly influencing extent of participation of respondents.